Biquadratic equations over p-adic fields - Saburov, Mansoor; Ahmad, Mohd Ali Khameini (2014)
In this paper, we study a bi-quadratic equation x^4 + ax^2 = b over p-adic fields Q_p. It is worth of mentioning that the bi-quadratic equation x^4 + 1 = 0 is not solvable in the real number field R. However, the same bi-quadratic equation x^4 + 1 = 0 is solvable some p-adic fields such as p = 17, 41, ... Therefore, it is of independent interest to provide a solvability criterion of a bi-quadratic equation over p-adic fields. In this paper, we shall provide a solvability criterion of bi-quadratic equations in terms of a,b.